2012
DOI: 10.1044/aac21.2.56
|View full text |Cite
|
Sign up to set email alerts
|

AAC Text Messaging

Abstract: Text messaging is becoming an increasing popular social networking strategy. More than 80% of American adults have cell phones, three-quarters of them send and receive text messages. People who rely on AAC are also finding texting an efficient, asynchronous way to communicate. In this report, Michael Williams discusses his use of texting. We also introduce core vocabulary resources for AAC texting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…28 Information and communication technologies have provided important options for a variety of AAC users. [36][37][38] For in-person interactions, writing or typing in advance and then showing the results to conversational partners is one option. 15 Writing in the moment is another.…”
Section: Speech For Autistic Adultsmentioning
confidence: 99%
“…28 Information and communication technologies have provided important options for a variety of AAC users. [36][37][38] For in-person interactions, writing or typing in advance and then showing the results to conversational partners is one option. 15 Writing in the moment is another.…”
Section: Speech For Autistic Adultsmentioning
confidence: 99%
“…This is why communicating is an action word. (Staehely, 2000, p. 3) All individuals who require AAC are impacted by environmental factors, but the extent of the impact will vary across individuals depending on their intrinsic communication resources: Those with strong linguistic, operational, social, and strategic skills and well-developed psychosocial factors will be less vulnerable to environmental barriers and constraints than those who are beginning communicators or who experience signifi cant language/cognitive limitations (McNaughton & Light, 2013;Williams, Beukelman, & Ullman, 2012). According to Beukelman and Mirenda (2013), environmental barriers and supports may cut across a range of domains including policy, practice, attitude, knowledge and skill barriers or supports.…”
Section: Environmental Supports and Barriersmentioning
confidence: 99%
“…187). In fact, with the advent of social media and a new arsenal of tools to link people together, there is increased emphasis in society on establishing, maintaining, and developing social connections across a wide ranging network (Sundqvist & Ronnberg, 2010;Williams et al, 2012).…”
Section: Changes In the Scope Of Communication Needsmentioning
confidence: 99%
“…In terms of symbolic targets, it has been suggested that initial vocabularies meet communication needs across learning, employment, living, and community contexts including health care settings by selecting common core vocabularies across these contexts (Banajee, DiCarlo, & Stricklin, 2003; Bryen, 2008; Williams, Beukelman, & Ullman, 2012). A core vocabulary consists of words common to the vocabularies of peers, is based on the language inventories of typically developing peers and does not change across environments or between individuals (Banajee et al, 2003).…”
Section: Intervention Guidancementioning
confidence: 99%